Une question de temps : apprentissage par problème dans un cours de police scientifique - Céline Weyermann; Amaury Daele; Cyril Muehlethaler; Romain Voisard (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
This article presents the evaluation of a problem-based learning (PBL) scenario introduced in a forensic course on dating and reconstruction of chronologies. The educational project comprises replacing part of the traditional lecture by PBL for practical reasons as well as conceptual. Evaluating the scenario highlighted that students’ motivation is enhanced by the problems put foward, stemming from real situations similar to those students will encounter in their future professional environment. Students also learned to work in groups and interact with their colleagues, thus being partners of their learning instead of sole receivers. This new approach of teaching concept and theories also improved the teacher capacities in enabling the learning process, and in particular transfering theory to practice.